Menstrual hygiene management among adolescent girls in India: a systematic review and meta-analysis. Issue 3 (2nd March 2016) - van Eijk, Anna Maria; Sivakami, M; Thakkar, Mamita Bora; Bauman, Ashley; Laserson, Kayla F; Coates, Susanne; Phillips-Howard, Penelope A
Abstract : Objectives: To assess the status of menstrual hygiene management (MHM) among adolescent girls in India to determine unmet needs. Design: Systematic review and meta-analysis. We searched PubMed, The Global Health Database, Google Scholar and references for studies published from 2000 to September 2015 on girls' MHM. Setting: India. Participants: Adolescent girls. Outcome measures: Information on menarche awareness, type of absorbent used, disposal, hygiene, restrictions and school absenteeism was extracted from eligible materials; a quality score was applied. Meta-analysis was used to estimate pooled prevalence (PP), and meta-regression to examine the effect of setting, region and time. Results: Data from 138 studies involving 193 subpopulations and 97 070 girls were extracted. In 88 studies, half of the girls reported being informed prior to menarche (PP 48%, 95% CI 43% to 53%, I 2 98.6%). Commercial pad use was more common among urban (PP 67%, 57% to 76%, I 2 99.3%, n=38) than rural girls (PP 32%, 25% to 38%, I 2 98.6%, n=56, p<0.0001), with use increasing over time (p<0.0001). Inappropriate disposal was common (PP 23%, 16% to 31%, I 2 99.0%, n=34). Menstruating girls experienced many restrictions, especially for religious activities (PP 0.77, 0.71 to 0.83, I 2 99.1%, n=67). A quarter (PP 24%, 19% to 30%, I 2 98.5%, n=64) reported missing school during periods. A lower prevalence of absenteeism was associated with higher commercial pad use in univariate (p=0.023) but not in multivariate analysis when adjusted for region (p=0.232, n=53). Approximately a third of girls changed their absorbents in school facilities (PP 37%, 29% to 46%, I 2 97.8%, n=17). Half of the girls' homes had a toilet (PP 51%, 36% to 67%, I 2 99.4%, n=21). The quality of studies imposed limitations on analyses and the interpretation of results (mean score 3 on a scale of 0–7). Conclusions: Strengthening of MHM programmes in India is needed. Education on awareness, access to hygienic absorbents and disposal of MHM items need to be addressed. Trial registration number: CRD42015019197.